Investigation of photophysicochemical properties of zinc phthalocyanines conjugated to metallic nanoparticles - Dube, Edith; Oluwole, David, O; Nyokong, Tebello; Nwaji, Njemuwa; Mack, John (Journal of Photochemistry and Photobiology A: Chemistry, 2020)
The syntheses of zinc(II) tetra–[3–(4–phenoxy) (propanoic acid) phthalocyanine] (2) and zinc(II) mono–[3–(4–phenoxy) (propanoic acid) phthalocyanine (3) are reported in this work. Compounds 2 and 3 were covalently linked to glutathione capped silver (AgNPs–GSH), gold (AuNPs–GSH) and silver-gold alloy (Ag3Au1NPs–GSH) nanoparticles (NPs) via an amide bond formation to afford the conjugates: 2–AgNPs–GSH, 3–AgNPs–GSH, 2–AuNPs–GSH, 3–AuNPs–GSH, 2-Ag3Au1NPs–GSH and 3-Ag3Au1NPs–GSH. The photophysicochemical behaviours of the compounds and their conjugates with NPs were assessed in solution. The conjugates afforded a decrease in fluorescence quantum yields and lifetimes with improved triplet quantum yields in comparison to the compounds. Accordingly, the AgNPs and AuNPs conjugates with the compounds afforded high singlet quantum yields. On the contrary, the conjugates of the alloy afforded decreased singlet quantum yields probably due to the screening effect. The compounds and their conjugates with NPs could serve as a viable and efficacious photosensitizer for photodynamic therapy.